Zwischen fordernder Natur und freiem Willen: Das politische an der klassischen deutschen Geographie - Schultz, Hans-Dietrich (ERDKUNDE, 2005)
Historians writing the history of the German national movement emphasize that those involved had only a vague imagination of the spatial extension of the German nation. Nevertheless, leading representatives of the movement as ARNDT and JAHN have formulated relatively detailed statements about the natural borders (e.g. seas and mountains) enclosing the German nation. In case both borders do not match they preferred the criterion of a geographical borderline and not the extension of the German language. The physical map showed directly what otherwise could not be seen as one complex: the Germans naturally determined homeland. Among others Geography, then reconstitutioning as a Länderkunde, supported the idea. Countries were not states but natural entities functioning as natural “vessels” for the nations. Anyway, according to what geographers thought to have learned from history they were supposed to become states which gradually happened. The natural borders of Germany, as defined by the Länderkunde in the first half of the 19th century, all in all matched those depicted by the German national movement. Both supported each other. Later historical developments have caused modifications. Today it is undoubtedly true that the surface of the earth carries no political relevance. There is no defining relation between the physical map and the political map. Political projects have to be based and decided on political arguments and can not refer to a “plan of nature